Scaling community seedbanks and farmer seed enterprises in East and Southern Africa: Workshop Highlights, 2-4 October 2019, Entebbe, Uganda - Adokorach, Joyce; Vernooy, Ronnie; Kakeeto, Ronald (2020)
The Scaling Community Seed Banks and Farmer Seed Enterprises in East and Southern Africa workshop was held in Entebbe, Uganda on 2-4 October 2019, to share experiences about community seed bank management and to develop national pilot scaling proposals. The workshop was organized under the umbrella of the Resilient Seed Systems for Climate Change Adaptation and Sustainable Livelihoods in East Africa project. Participants from Ethiopia, Kenya, Uganda, Zambia and Zimbabwe discussed strengthening their community seed banks’ capacity development on topics such as documentation and record keeping, data management and sharing, seed production, entrepreneurship, development of a portal and/or App for online distribution of seed, advocacy and policy development, gender action learning, and policy support for community seed banks and farmer seed enterprises. Workshop presentations showcased the status of the community seed banks in Ethiopia, Kenya, South Africa, Uganda, Zambia and Zimbabwe; and the status of farmer seed enterprises in Uganda and Zimbabwe. Thematic presentations addressed policy issues, gender, the use of Information and Communication Technologies (ICTs), and the development of a seed knowledge/service hub. Presentations on pratical field experiences from Uganda were made (including demonstrations of seed collections) by the Soroti Community Seed Bank, and the Joy and Family demonstration farm in Ngoma, Kiziba, Kagano-Sheema. The workshop resulted in the production of three pilot scaling proposals for community seed bank/farmer seed enterprises in Kenya (led by the Seed Savers Network), Uganda (led by NARO) and Zambia (led by the Zambia Agriculture Research Institute, ZARI), and supported by the Ethiopian Biodiversity Institute (EBI) and the Community Technology Development Trust (CTDT) Uganda.